Research progress on novel nanomaterials mediated treatment of candidal keratitis - ZHAO Tianqi; LIU Lian (Yanke Xuebao)
Fungal keratitis is a prevalent blinding ocular disease in China, with Aspergillus, Fusarium, and Candida ranking as the top three pathogenic fungi. As an opportunistic pathogenic fungus, Candida readily causes opportunistic infections when host immunity is compromised or the ocular surface microenvironment is imbalanced. The incidence of Candida keratitis has been rising annually due to factors such as the misuse of immunosuppressive drugs and increased contact lens wear. Following infection, Candida itself and the formation of biofilms contribute to enhanced resistance against currently used systemic antifungal agents, including voriconazole, amphotericin B, itraconazole, and fluconazole,posing significant challenges to clinical treatment.Recently, research on nanomaterials-mediated drug delivery systems for treating Candida keratitis has burgeoned. Novel nanomaterials, serving as carriers for antifungal drugs, enhance therapeutic efficacy by improving drug solubility, prolonging ocular surface retention time, penetrating biofilms, and enhancing corneal permeability. These advancements offer new strategies to address drug resistance in Candida infections.This article reviews the research status and progress of emerging nanomaterials—such as nanopolymers, nanoparticles,nanogels, liposomal carriers, nanocubes, nanoneedles, and nanomicelles—as innovative drug delivery vectors for Candida keratitis. By overcoming the limitations of conventional therapies, these nanomaterials provide feasible solutions to the clinical challenges of limited antifungal options and drug resistance. The integration of nanotechnology holds promise for revolutionizing the treatment of Candida keratitis and advancing precision medicine for ocular surface fungal infections.